Clustered protocadherins - Chen, Weisheng V.; Maniatis, Tom (Development (Cambridge), 2013)
The majority of vertebrate protocadherin (Pcdh) genes are clustered in a single genomic locus, and this remarkable genomic organization is highly conserved from teleosts to humans. These clustered Pcdhs are differentially expressed in individual neurons, they engage in homophilic trans-interactions as multimers and they are required for diverse neurodevelopmental processes, including neurite self-avoidance. Here, we provide a concise overview of the molecular and cellular biology of clustered Pcdhs, highlighting how they generate single cell diversity in the vertebrate nervous system and how such diversity may be used in neural circuit assembly.